Job Satisfaction and Professional Commitment in Early Childhood Education Teachers - Umi Anugerah Izzati; Gunarti Dwi Lestari; Wulan Adiarti (Journal of Nonformal Education, 2024)
Early childhood education is an important foundation for a child's future development. For this reason, when learning at the early childhood education level, teachers are needed who have professional commitment in carry-ing out their duties. Teachers who have professional commitment will be able to display optimal performance for early childhood learning. There are many factors that influence professional commitment, one of which is job satisfaction. Job satisfaction factors are the topic of study in this research. This research aims to determine the relationship between job satisfaction and professional commitment in early childhood education teachers.  This research was conducted using quantitative methods. The sampling technique for this research uses convenience. The number of research subjects was 120 Early Childhood Education teachers. Data were collected using a psy-chological scale developed by the research team. The psychological scale consists of a job satisfaction scale and a professional commitment scale. Data analysis was carried out using the Pearson Correlation analysis tech-nique. The research results show that there is a significant positive relationship between job satisfaction and professional commitment in early childhood education teachers. The results of the correlation analysis show that the higher the job satisfaction, the higher the professional commitment. The novelty of this research is that there is still limited research regarding the relationship between job satisfaction and professional commitment among early childhood teachers. Several previous studies discussing job satisfaction and professional commitment used research subjects, such as nurses, auditor, employees and teachers at higher education levels.